2018
DOI: 10.1136/bmjopen-2018-022164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of group practices on patients, physicians and healthcare systems: protocol for a scoping review

Abstract: IntroductionGroup practices have potential benefits for patients, physicians and healthcare systems. Although group practices have been around for many years, research in this area is lacking and generally is centred around the economic benefits that may be realised from group practice. The aim of this scoping review is to identify the impact that group practices have on patients, physicians and healthcare systems to guide further research in this area.Methods and analysisA scoping review will be performed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…A complete scoping review protocol was developed and published. 28 The following stages were incorporated into this scoping review according to what is suggested by Levac et al : identifying the research question; identifying relevant studies; study selection; charting the data; collating, summarising and reporting results; and consultation. Full details on each stage can be found in the published protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete scoping review protocol was developed and published. 28 The following stages were incorporated into this scoping review according to what is suggested by Levac et al : identifying the research question; identifying relevant studies; study selection; charting the data; collating, summarising and reporting results; and consultation. Full details on each stage can be found in the published protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Full details on each stage can be found in the published protocol. 28 Briefly, MEDLINE, EMBASE and Cochrane Central were searched from database inception to October 2018 to identify relevant studies that assess the impact of group practices on patient care, satisfaction and outcomes; physician quality of life, satisfaction and income; and healthcare system finances. There were no restrictions placed on publication date.…”
Section: Methodsmentioning
confidence: 99%
“…While much emphasis has been placed on describing and implementing inter-disciplinary and multidisciplinary care, 5 9 there has been limited progress in defining the mechanics of intra -disciplinary collaboration to achieve team-based shared care. 10 Intra-disciplinary collaboration occurs when surgeons within the same discipline are embedded in each other’s practice to enhance knowledge transfer, develop skills, and deliver better patient care. Intra-disciplinary collaboration is the crux of team-based shared care; the capabilities of the collective are harnessed for shared clinical care, professional development, and to overcome bottlenecks in administrative processes related to resource allocation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…3 Whenever single-entry and team-based models of care have been introduced in health care, they have been widely embraced and valued by patients and health care providers; Canadian examples include obstetrics, cardiac surgery, joint replacement, transplantation, cancer surgery, acute care and elective general surgery. 3,5,6 Furthermore, singleentry models are overwhelmingly preferred by referring physicians. 7 Advocates of these models emphasize how they reduce and harmonize wait times for specialist care and elective surgery.…”
mentioning
confidence: 99%